Relationship of Energy Intake, Macro and Micro Nutrients to Physical Fitness of Athletes of Dyva Taekwondo Centre Cibinong - Mury Kuswari; Fitri Handayani; Nazhif Gifari; Rachmanida Nuzrina (JUARA : Jurnal Olahraga, 2020)
Physical Fitness is the ability to do daily activities easily, without getting tired excessive, and has a power reserve to rest. VO2max is a main factor for athletes in order to get a good performance. This study aims to determine the relationship of energy intake, macro and micro nutrients to physical fitness of athletes of Dyva Taekwondo Centre Cibinong. This study used cross sectional design research. The number of respondents was 30 athletes determined by total sampling. The consumption energy and macronutrients were measured by 3x24 hour recall method, whereas intake of micronutrients data was obtained using semy FFQ. Variable relationships were tasted using Pearson Correlation. The result showed that the average age of respondents was 14±1 years, energy intake 2259±571 kkal, protein 73±15 g, fat 51,7±8,9 g, carbohydrate 259±57 g, vitamin B1 1,15±0,4 mg, vitamin C 230±81,7 mg, fe 21±4,5 mg and fitness level 35,69±7,2 kg/ml/minute. There was relationship of energy intake (p= 0,0001), carbohydrate (p=0,0001), vitamin C (p=0,0001), fe (p=0,007 and fitness level. There was no correlation between fat intake, protein, vitamin B1 and fitness level (p=0,081, p=0,497, p=0,383). Intake of energy, carbohydrate, vitamin C, and fe does relate to physical fitness of athletes of Dyva Taekwondo Centre Cibinong. Athletes are advised to consume food according to their daily needs in order to maintain their fitness therefore, they can achieve optimal performance.